The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3899/jrheum.140853
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Serious Infections and Malignancies Among Patients with Rheumatoid Arthritis Receiving Either Tumor Necrosis Factor Inhibitor or Rituximab Therapy

Abstract: Our results provide some reassurance of the safety of biologic treatments in the treatment of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 23 publications
2
40
0
2
Order By: Relevance
“…In total, and considering the previous evidence from 2013,6 15 studies, 7 at low risk of bias, compared the risk of serious infections between bDMARDs and csDMARDs and overall found a significantly increased risk with adjusted HRs (aHR) between 1.0 and 1.8 per study 10–15 35–43. More recent studies at low risk of bias did not show an increased risk 10 14. One study comparing bDMARDs with the general population reported standardised incidence rates of 16–20 for tumour necrosis factor-α inhibitor (TNFi) and even higher for RTX (table 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In total, and considering the previous evidence from 2013,6 15 studies, 7 at low risk of bias, compared the risk of serious infections between bDMARDs and csDMARDs and overall found a significantly increased risk with adjusted HRs (aHR) between 1.0 and 1.8 per study 10–15 35–43. More recent studies at low risk of bias did not show an increased risk 10 14. One study comparing bDMARDs with the general population reported standardised incidence rates of 16–20 for tumour necrosis factor-α inhibitor (TNFi) and even higher for RTX (table 1).…”
Section: Resultsmentioning
confidence: 98%
“…9 10 14 25 51–55 Both in comparison to the general population and to patients on csDMARDs, patients on bDMARDs did not show an increased risk for malignancies. In a few more recent studies, patients on non-TNFi were also included 9 10.…”
Section: Resultsmentioning
confidence: 99%
“…In a German study, the crude incidence rates per 1,000 person-years were reported to be 5.1 for TNF inhibitors as a class and 7.2 for anakinra (47). In a cohort of Finnish RA patients, the crude rates (95% CI) for malignancy per 1,000 person-years were 5.9 (2.8-11) for infliximab, 7.4 (4.6-11) for etanercept, 6.1 (3.5-9.9) for adalimumab, and 8.4 (3.1-18) for rituximab (35). Strength of evidence for malignancies was low.…”
Section: Resultsmentioning
confidence: 99%
“…В рамках финского национального регистра (National Register for Biologic Treatment in Finland и Central Finland Central Hospital) [29] были проанализированы материалы применения БПВП (n=1400), ИНФ (n=642), ЭТЦ (n=1245), АДА (n=1207) и РТМ (n=438), касающиеся час-тоты серьезных инфекций, требующих госпитализации на фоне лечения ГИБП и БПВП. Риск инфекций составил 1,2 (95% ДИ 0,63-2,3) для ИНФ, 0,84 (95% ДИ 0,53-1,3) для ЭТЦ, 0,98 (95% ДИ 0,60-1,6) для АДА и 1,1 (95% ДИ 0,59-1,9) для РТМ.…”
Section: регистр Gerinisunclassified